Harmonic response from microscopic antibubbles. (August 2018) - Postema, Michiel; Novell, Anthony; Sennoga, Charles; Poortinga, Albert T.; Bouakaz, Ayache
Abstract: An antibubble is a gas bubble containing a liquid droplet core. Both the droplet and the gas bubble are typically surrounded by stabilising shells. Owing to electrostatic forces exerted by these shells, core droplets of micrometer diameter do not readily coalesce with the surrounding liquid medium. Owing to the incompressibility of the liquid droplet core, antibubbles will oscillate asymmetrically, i.e., the radial excursion amplitude of the surface is greater during expansion than during contraction, when subjected to diagnostic ultrasound. Consequently, the harmonic content of the ultrasound signal radiated from antibubbles must be higher than that from identical bubbles without a liquid core. Whether the harmonic signal component generated by physical antibubbles is higher than the harmonic component of identical bubbles without a core has been studied here. We subjected prefabricated antibubbles and identical bubbles without core droplets to 1-MHz ultrasound and to a commercial ultrasound system, and recorded the spectra with a broadband transducer oriented perpendicularly to the transmitter. Normalised by the acoustic response from the medium, the antibubble signal shows stronger higher harmonics than the reference signal, and negligible fundamental response. In conclusion, antibubbles are suitable candidates for harmonic imaging. The generation of higher harmonics without fundamental has been attributed to asymmetric antibubble expansion.